KEKERASAN DAN PROBLEMATIKA DIALOG ANTAR UMAT BERAGAMA - Mawardi Mawardi (TOLERANSI: Media Ilmiah Komunikasi Umat Beragama, 2010)
This article declares that violence of religions because of sacred text, dogma and the interpretation of text. Absolutely versus relatively, and humanism versus god. Violenceof religions departs from ulama, pastor, religious leader, missionaries and religious teacher, religions ambivalence between peace and violence, because in the religion on text and context are very rigid. The holy war was justified by religious text. Among problems of religious dialogue are collective identity, minority and majority issues, Christianization and islamization issues, and the conversion of religion. Continued dialogue with cutting crucial issues, collective identity, minority-majority, Christinization and Islamization and conversion.